Efficacy of pharmacological interventions and therapeutic exercises for rheumatoid arthritis: a systematic review and meta-analysis - Adeyemi, Timothy; Chukwuike, Vitalis Ikenna; Oladimeji, Motunrayo Adebukunola; Ahwinahwi, Ufuoma Shalom; Ayeni, Victor Ayodeji; Abdullahi, Aisha Adam; Isah, Abdulmuminu; Ayamolowo, Love Bukola; Okeke, Oluchukwu Perpetual; Abodunrin, Olunike; Akinsolu, Folahanmi; Sobande, Olajide Odunayo (Frontiers in Pharmacology, 2025)
BackgroundRheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by persistent synovitis, systemic inflammation, and progressive joint damage. Medication and physical exercise are the most common interventions documented for the treatment of RA. The current systematic review examined the efficacy of pharmacological and physical exercise interventions for RA.MethodsA systematic literature search utilized databases (PubMed, Web of Science, Google Scholar, Scopus, and CINAHL) to identify relevant randomized controlled trials (RCTs). The search strategy included keywords related to rheumatoid arthritis, pharmacological interventions, exercise therapy, and clinical outcomes. The review was registered with PROSPERO (CRD42024587378). Two independent reviewers screened the identified articles, and relevant data were extracted for analysis. The quality of evidence for the outcomes of interest in this systematic review and meta-analysis was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) framework. Meta-analysis was carried out using a random-effects model. For the meta-analysis, we assessed the heterogeneity using the I2 statistic.ResultsEighteen RCTs with a total sample size of 7,062 were included. Of these, eleven studies (61.11%) investigated the efficacy of different pharmacological interventions, whereas seven (38.89%) assessed the effects of exercise interventions. Different exercise programs showed improved functionality, reduced pain, and improved patient quality of life (QoL), while short- and medium-term sensorimotor trainings were reported. Pharmacological interventions also reported varying levels of reduction in disease activity and improved functionality. Pooled effects of four studies included in the meta-analysis revealed the different categories of incremental clinical outcomes (1.89, 2.46, and 2.63) after 24 months based on the American College of Rheumatology (ACR) criteria—ACR 20, ACR 50, and ACR 70, respectively. Significant effect sizes (0.09 and −0.08) after 24 weeks were equally found in three studies, indicating the reduction in disease activity and an improvement in functionality, respectively. Despite robust efficacy data, a major limitation across the literature is the heterogeneity of reported ACR outcomes, attributable to pharmacological variation (immunogenicity and disease stage) rather than purely statistical bias.ConclusionPharmacological and physical exercise interventions benefit many patients with RA, particularly regarding clinical outcomes such as reduced disease activity and improved functional ability; and both interventions are potentially synergistic in RA. However, more RCTs are required, especially in Sub-Saharan Africa (SSA), to buttress the evidence base for these interventions. Crucially, the review notes the need for greater pharmacological discussion on safety and tolerability in future studies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024587378.